VETERINARY ETHOLOGY APPLIED TO A DAIRY GOAT HERD: CLASS REPORT (Environmental Smoke, 2024)
Environmental stress on farm animals is a limiting factor for all livestock farming. In this sense, the action of professionals, such as veterinarians is essential to outline the best management and the best actions to develop with livestock in a region.In this manner the results from the study performed by Furtado (2007) presented information on the behavior of dairy goats that favor new evaluations. The influence of the environment on the behavioral parameters of dairy goats was observed in Lajes do Cabugi, Rio Grande do Norte, on a dairy goat production farm.Ethology is a science that favors the understanding of the adaptation of animals (i.e. behavior) to the environment in which they are found. Therefore, this knowledge field helps the veterinarian in the clinical assessment of animals’ health and well-being, promoting animal aid to achieve greater productivity, which is one of the objectives of the animals' actions professionals.Through research carried out in a brief bibliographical-secondary survey, the objective of this study is to evaluate the recorded ethogram of a goat herd, which had been exposed at two different times of breeding.The environmental variations recorded at the beginning and end of the experiment (June and September 2007) were, respectively: i) ambient temperature 25.82ºC and 25.88 ºC; ii) relative humidity 67.48% and 66.64%. The outcome obtained with ethogram was that the animals had many more episodes of lying under the shade in August compared to June, as well as grazing in the shade, brooding in the shade, standing still in the shade and walking. These results show that the herd spent much more energy to maintain homeostasis under heat stress (FURTADO; SILVA; TELES, 2018; GAIA et al., 2019).It was concluded that the herd must be relocated in terms of access to nutritional supplementation with hay and concentrates, have access to more shaded areas and promote relocation in grazing and stabling hours, with the aim of preventing pathologies linked to heat stress, as well as having a better quality of life and animal well-being.